Y-chromosome R-M343 African lineages and sickle cell disease reveal structured assimilation in Lebanon - Haber, Marc (2011)
We have sought to identify signals of assimilation of African male lines in Lebanon by exploring the association of sickle cell disease (SCD) in Lebanon with Y-chromosome haplogroups that are informative of the disease origin and its exclusivity to the Muslim community. A total of 732 samples were analyzed, including 33 SCD patients from Lebanon genotyped for 28 binary markers and 19 short tandem repeats on the non-recombinant segment of the Y chromosome. Genetic organization was identified using populations known to have influenced the genetic structure of the Lebanese population, in addition to African populations with high incidence of SCD. Y-chromosome haplogroup R-M343 sub-lineages distinguish between sub-Saharan African and Lebanese Y chromosomes. We detected a limited penetration of SCD into Lebanese R-M343 carriers, restricted to Lebanese Muslims. We suggest that this penetration brought the sickle cell gene along with the African R-M343, probably with the Saharan caravan slave trade.